Clinical prediction scores for ruptured appendicitis in acute appendicitis patients - Senavat, Preeyapon; Jearwatanakanok, Kijja (Journal of Nakornping Hospital, 2020)
Objective: The aim of this study was to develop a scoring system for predicting the ruptured appendicitis in acute appendicitis patients using various determinants. Patients and methods: The study was a diagnostic prediction study. We included all age >15 years patients who had a confirm diagnosis of acute appendicitis, got appendectomy surgery and had pathology result at Nakornping Hospital during January to December 2018. We collected data, comparison of risk factors between ruptured appendicitis and non-ruptured appendicitis. All risk factors were analyzed and transformed into item scores. All item scores were added together for a total score. The total scores were used as a predictor for ruptured appendicitis in acute appendicitis patients. Results: A total of 499 patients with acute appendicitis were included in the study and used for identifying risk factors of ruptured appendicitis in acute appendicitis patients in the final analysis model. Five factors were identified and used for developing the clinical prediction scores, and the factors were as follow: male(adjusted OR=8.42, P<0.001), age >20-60 years (adjusted OR=2.56, P=0.005) and age >60 years (adjusted OR=3.67, P=0.001), duration of onset abdominal pain to hospital >24hr.(adjusted OR=1.96, P=0.005), heart rate >=130 beats/min(adjusted OR=8.58, P=0.005) and localized rebound tenderness right lower quadrant(adjusted OR =1.51, P=0.092). Prediction scores ranged from 0 to 16 and divided in to 3 groups. A high-risk group (score >= 11) predicted a high possibility of ruptured appendicitis (LR+=12.15, P<0.001). An intermediate-risk group (score 6-10) predicted a moderate possibility of ruptured appendicitis (LR+=1.70, P<0.001). A low-risk group (score <= 5) predicted a low possibility of ruptured appendicitis (LR+=0.22, P<0.001). The performance of the scoring model was 77.98% (area under the ROC, (95% CI=1.38-1.67)). Conclusion: It is possible to predict the risk of ruptured appendicitis in acute appendicitis patients with this score. The score can be used as a guideline for decision making in referring patient to appropriate medical center, appropriate treatment and informing the patient and their families.